Growth and productivity of rice as influenced by nitrogen levels and its split application in North Eastern Hilly Region - Chandrabhan Bharti; Vishram Ram (Annals of Agricultural Research, 2023)
In Meghalaya, most of the nitrogen (N) fertilizer applied is prone to losses through leaching and runoff owing to high rainfall and terrace lands. With reduced application and increased split application, the utilization rate of nitrogen could be enhanced. Moreover, newly developed rice varieties are known to be fertilizer responsive with better nutrient translocation ability from source to sink compared to common rice which requires standardisation of appropriate rate of nitrogen fertilizer to be applied. In this backdrop, one ûeld experiment(..) with 5 N levels such as 0, 30, 60, 90, 120, 150kg ha-1 and 3 split application with (..) Shahsarang variety during 2018-19 and 2019-20. The results showed that with the increase in N dose with different splitting time, the number of tillers, dry matter production, test weight along with grain and straw yieldswere increased while the harvest index (HI), decreased beyond 120 kg N ha-1. Additionally, with the increase of N application, the grain yield and harvest index (HI) of rice followed a parabolic trend.